DYNAMICS OF COVID-19 SYMPTOMS AND CHANGES IN Ct VALUES OF RdRp, N AND E GENES IN 1044 PATIENTS POSITIVE FOR SARS-CoV-2 - Mariya Sredkova; Cvetan Popov; Georgi Golemanov; Pencho Tonchev; Vladislav Nankov; Alexander Blazhev; Antoniya Popova; Radostina Mogilska; Valeri Delcheva; Eleonora Kuteva (Peytchinski Publishing, 2022)
Purpose: To describe clinical characteristics of patients positive simultaneously for RdRp, N and E genes of SARS-CoV-2 and to analyse dynamics of symptoms and Ct values in the interval from day 0 to day 10 after symptoms onset. Materials and methods: Retrospective analysis of data obtained on the day of specimen collection from 1044 individuals was carried out. Detection of RdRp, E and N genes of SARS-CoV-2 was conducted by RT-PCR. Only patients positive for all three genes were included. Results: Out of all patients, 47.8% were female, and 52.2% were male with a median age of 60 years, and the elder (>50 years) population constituted 71.5%. The most common comorbidities were cardiovascular disease (44.5%), diabetes mellitus (11.0%), and chronic pulmonary disease (8.6%). The prevalent symptoms at the time of specimen collection were fever (74.7%), cough (67.1%), and dyspnea (39.6%). Fever and cough were leading symptoms in the time interval between zero and the tenth day since the onset of COVID-19. A linear trend for dry cough and dyspnea, with a daily increase of 2.2% and 2.3%, respectively, was observed. Dry cough was the primary discriminator in distinguishing mild and moderate infection. Gradual increase of Ct values of all genes was observed from day 0 to day 10, and day 3 was essential for separating two time intervals. Conclusions: Flu-like symptoms were leading over the study period. Male sex, older age, cardiovascular disease, diabetes mellitus, and chronic pulmonary disease were risk factors for infection. Cough, age over 65 years and male sex in the group 33-63 years were predictors of more severe disease.